KONSENTRASI FOSFOR PADA BERBAGAI UMUR FISIOLOGI DAUN KAKAO (Theobroma cacao L.) KEBUN RAKYAT - Priyanto, Iklan; Tjoa, Aiyen; Kadekoh, Indrianto (AGROTEKBIS, 2018)
This study aimed to determine P concentration at various leaf physiological age and the availability of soil P on smallholder cocoa plantations. Cacao leaf samples were taken by purposive sampling at two villages namely Bobo and Maku. The soil samples were taken at 0-30 cm layer from the cacao crown area of similar trees where the leaves were taken. The data obtained was analyzed using regression test and T test. This study indicated that the soil P concentration in the Bobo and Maku villagesis positively correlated to the P concentration at various leaf physiological age. P concentration of young leaves, adult leaves and senesens leaves in Bobo Village and Maku Village had significantly different values,where the P concentration of young leaves is higher than the adult and senesensleaves. The average P concentration of the cocoa leaf and P available in Bobo and Maku Village had significant differences where the highest leaf P concentration was found in Bobo Village while the highest available P concentration in soil was found in Maku village.